Social Capital Reciprocity and Women Pillars of Family Economy - Rahel Widiawati Kimbal; Johnny Manaroinsong; Jaqualine Tangkau (AIBPM Publisher, 2021)
This research aims to find forms of women's reciprocity social capital as a pillar of the family economy. This study uses a qualitative research method with a case study whose data collection techniques use triangulation in the form of observation, interviews and documentation. For data analysis using Miles and Huberman models. The results found in the field regarding the forms of social capital of women's reciprocity as pillars of the family economy at UIK were found through interactions and social relations between women business owners and women workers in the field in terms of: (1). Knowledge collaboration (2) free knowledge transfer (3) Support from family members (4) Cooperation and mutual encouragement between individuals (5) Helping each other (6) Motivating (7) having empathy for others and (8) Participating. These forms of reciprocity of women's social capital become the economic reinforcement of the family. Because the success of the family cannot be separated from the role of women as important actors. Therefore, it is hoped that the positive resources of women through the use of social capital reciprocity depicted in small industrial enterprises can be an inspiration for small businesses and women in Indonesia to keep working.